Hidden morphology of Shackleton Crater, lunar South Pole - Mitusov, Andrey V.; Stark, Alexander; Khrisanov, Vladislav R.; Oberst, Jürgen (Planetary and Space Science, 2023)
The article's goal is the detailed description of geomorphologic structures on the floor and interior walls of Shackleton Crater and a reconstruction of their formation histories. A Digital Elevation Model (DEM) with 20 m grid was constructed for the area around the crater based on Lunar Orbiter Laser Altimeter (LOLA) data. The DEM was analysed for slope steepness, Maximal Catchment Area (MCA) and four curvatures: maximal (kmax), minimal (kmin), horizontal (kh) and vertical (kv). Using this extensive set of Morphometric Variables (MVs) for the first time for a detail lunar DEM revealed unknown structures in permanently shaded areas. The previously identified large elevated structures “A" and “C" are attributed to landslides. “A" is related to a relatively large meteoroid impact that produced a recognisable crater on the exterior slope of Shackleton. “C" is associated with a landslide scar affecting the rim of Shackleton Crater directly above it. Structure “B” is not related to landsliding, but without of additional high-resolution geophysical data, its origin remains unclear. The low number of small impact craters on the steep slopes and sediment fields indicates ongoing surface erosion due to migration of unconsolidated fine grains and their deposition downslope. The foot slope zone is characterised by multiple accumulations of debris flows in the form of thin strips, identified as local landforms with kh > 0. On the surface of elevated structures “A”, “B” and “C” the map of kh reveals tree-like structures – erosion forms previously unknown in lunar geomorphology. These structures are formed by branching spurs characterised by several orders. The spurs are located relatively perpendicularly to the altitude isolines. The thickest (up to 120 m) slope deposits form a relatively flat area between the elevated structure “B" and the crater wall. These deposits should be of the greatest interest for future investigations searching for buried volatiles mixed with slope deposits.